2016
DOI: 10.1128/mbio.01248-16
|View full text |Cite
|
Sign up to set email alerts
|

Complete and Incomplete Genome Packaging of Influenza A and B Viruses

Abstract: The genomes of influenza A and B viruses comprise eight segmented, single-stranded, negative-sense viral RNAs (vRNAs). Although segmentation of the virus genome complicates the packaging of infectious progeny into virions, it provides an evolutionary benefit in that it allows viruses to exchange vRNAs with other strains. Influenza A viruses are believed to package their eight different vRNAs in a specific manner. However, several studies have shown that many viruses are noninfectious and fail to package at lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 33 publications
3
54
1
2
Order By: Relevance
“…While this failure of protein expression could be explained by a failure in transcription or translation, the results of our single-cell sorting assay indicate that the vRNA segments themselves are absent, as they should be amplified by the helper virus polymerase even if they do not encode functional proteins. As in Brooke et al, our method does not discriminate between the alternative possibilities that segments are absent from virions themselves or are lost within the cell, but published results suggest that a single virion usually contains a full genome 22, 23 . Importantly, our single cell assay quantifies the frequencies of all eight segments, rather than only those that can be detected indirectly by staining for protein expression, and therefore allows for analysis of the associations between segments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While this failure of protein expression could be explained by a failure in transcription or translation, the results of our single-cell sorting assay indicate that the vRNA segments themselves are absent, as they should be amplified by the helper virus polymerase even if they do not encode functional proteins. As in Brooke et al, our method does not discriminate between the alternative possibilities that segments are absent from virions themselves or are lost within the cell, but published results suggest that a single virion usually contains a full genome 22, 23 . Importantly, our single cell assay quantifies the frequencies of all eight segments, rather than only those that can be detected indirectly by staining for protein expression, and therefore allows for analysis of the associations between segments.…”
Section: Discussionmentioning
confidence: 99%
“…Replication and expression of only a subset of the genome may be explained by two potential mechanisms: either the majority of particles lack one or more genome segments, or segments are readily lost in the process of infection before they can be replicated. Electron microscopy has shown that most particles contain eight distinct RNA segments 22 , and FiSH-based detection of viral RNAs indicated that a virion tends to contain one copy of each segment 23 , suggesting that most particles contain full genomes. Regardless of the molecular mechanisms that lead to the phenomenon of incomplete IAV genomes, their frequent occurrence suggests that complementation by co-infection at the cellular level is an underappreciated aspect of the viral life cycle.…”
mentioning
confidence: 99%
“…Previous studies support that IAV most likely contains a selective packaging mechanism (3942). IAV and IBV incorporate eight RNPs arranged in a specific pattern “1+7”, in which seven RNPs surround the central one (40, 43, 44). Surprisingly, artificially generated 7-segmented IAV, which lacks an HA segment, incorporated rRNA as the eighth RNP instead of an HA segment (37).…”
Section: Discussionmentioning
confidence: 99%
“…The NP and viral RNA associate in a non-uniform manner, where regions of the RNA are unbound by NP and capable of forming complex structures [5]. Macro-organization of vRNPs within the viral capsid show tight packaging, organized in a ‘7+1’ orientation, a single vRNP center shaft surrounded by seven others (46).…”
Section: Introductionmentioning
confidence: 99%